Perbandingan Efek Antibakteri Ekstrak Air Kopi Arabika dengan Ekstrak Air Dark Chocolate pada Kultur Bakteri Methicillin – Resistant Staphylococcus Aureus - Rifira Hanifah; Hendro Sudjono Yuwono; Rizki Perdana (Bandung Conference Series: Medical Science, 2024)
Abstract. The emergence of new strains of Methicillin-resistant Staphylococcus aureus (MRSA) has led to the need for alternative antibiotics, one of which comes from natural ingredients, namely arabica coffee and dark chocolate, which are known to have ingredients that act as antibacterials. The aim of the study was to compare the inhibition zone of arabica coffee water extract with dark chocolate water extract against MRSA bacteria. The method used was Kirby-Bauer disc diffusion consisting of treatment groups of arabica coffee water extract with concentrations of 50% and 100%, dark chocolate water extract with concentrations of 50% and 100%, positive control (vancomsin), and negative control distilled water. This study was conducted at the Microbiology Laboratory of the Faculty of Medicine, Padjadjaran University (FK Unpad) from October 2022 to December 2023. Data processing using ANOVA (Analysis of Variance) Post Hoc Games-Howell test with IBM SPSS 26 statistical application. The results showed that the average value of the largest inhibition zone was found in the positive control vancomycin which was 21.75 mm, then 100% arabica coffee extract which was 14.25 mm, 50% arabica coffee extract which was 9.75 mm. The 50% and 100% concentrations of dark chocolate aqueous extract did not form an inhibition zone, equivalent to the negative control. It is concluded that 50% and 100% arabica coffee water extracts have inhibitory ability while 50% and 100% dark chocolate water extracts do not have inhibitory ability. Abstrak. kemunculan galur baru Methicillin-resistant Staphylococcus aureus (MRSA) membuat dibutuhkannya alternatif antibiotik lain, salah satunya berasal dari bahan alam yaitu kopi arabika dan dark chocolate yang diketahui memiliki kandungan yang berperan sebagai antibakteri. Tujuan penelitian adalah membandingkan zona hambat ekstrak air kopi arabika dengan ekstrak air dark chocolate terhadap bakteri MRSA. Metode yang digunakan adalah difusi cakram kirby-Bauer yang terdiri dari kelompok perlakuan ekstrak air kopi arabika dengan konsentrasi 50% dan 100%, ekstrak air dark chocolate dengan konsetrasi 50% dan 100%, kontrol positif (vankomsin), dan kontrol negatif akuades. Penelitian ini dilakukan di Laboratorium Mikrobiologi Fakultas Kedokteran Universitas Padjadjaran (FK Unpad) pada bulan oktober 2022 sampai desember 2023. Pengolahan data menggunakan Uji ANOVA (Analysis of Variance) Post Hoc Games-Howell dengan aplikasi statistik. Hasil penelitian menunjukan rerata nilai zona hambat terbesar terdapat pada kontrol positif vankomisin yaitu 21,75 mm, kemudian ekstrak kopi arabika 100% yaitu 14.25 mm, ekstrak kopi arabika 50% yaitu 9.75 mm. Pada ekstrak air dark chocolate konsentrasi 50% dan 100% tidak terbentuk zona hambat, setara dengan kontrol negatif. Simpulan ekstrak air kopi arabika 50% dan 100% memiliki kemampuan daya hambat sedangkan ekstrak air dark chocolate 50% dan 100% tidak memiliki kemampuan daya hambat.